2018
DOI: 10.1073/pnas.1716804115
|View full text |Cite
|
Sign up to set email alerts
|

Mast cells promote small bowel cancer in a tumor stage-specific and cytokine-dependent manner

Abstract: SignificanceWe show that distinct subsets of mast cells (MCs) expand with sequential oncogenic events in small bowel cancer. Mucosal mast cells (MMCs) previously detected early during Trichinella spiralis infection expand in adenomatous polyps in an IL-10–dependent manner. Connective tissue mast cells (CTMCs), earlier shown to expand during the resolution of inflammation following clearance of T. spiralis, are independent of IL-10 and associate with the transition of polyps to adenocarcinoma. IL-33 upregulates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 37 publications
4
34
0
Order By: Relevance
“…In small intestinal cancers, MCs expand in benign polyps in the presence of IL-10, IL-13, and IL-33 as well as ILC2 cells. The presence of these MCs is maintained in an IL-10 dependent manner-overexpression of IL-10 greatly expanded MC populations in these polyps [59]. The presence of IL-10 in conjunction with MC chemokines and alarmins such as IL-33 explains the pro-cancer, pro-inflammatory role MCs can play in certain cancers; in the context of small bowel cancers, MC protease expression resembled MMCs but included CTMC-related mast cell proteases too [59].…”
Section: Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…In small intestinal cancers, MCs expand in benign polyps in the presence of IL-10, IL-13, and IL-33 as well as ILC2 cells. The presence of these MCs is maintained in an IL-10 dependent manner-overexpression of IL-10 greatly expanded MC populations in these polyps [59]. The presence of IL-10 in conjunction with MC chemokines and alarmins such as IL-33 explains the pro-cancer, pro-inflammatory role MCs can play in certain cancers; in the context of small bowel cancers, MC protease expression resembled MMCs but included CTMC-related mast cell proteases too [59].…”
Section: Cancermentioning
confidence: 99%
“…The presence of these MCs is maintained in an IL-10 dependent manner-overexpression of IL-10 greatly expanded MC populations in these polyps [59]. The presence of IL-10 in conjunction with MC chemokines and alarmins such as IL-33 explains the pro-cancer, pro-inflammatory role MCs can play in certain cancers; in the context of small bowel cancers, MC protease expression resembled MMCs but included CTMC-related mast cell proteases too [59]. When the polyps switched to an invasive phenotype, CTMCs expressing both MMC and CTMC proteases expanded, demonstrating cancer's ability to alter MC activity toward a pathogenic, pro-cancer function [59].…”
Section: Cancermentioning
confidence: 99%
“…The protease released by activated mast cells is the key factor in inducing angiogenesis, which may promote tumor angiogenesis and tumor growth [95]. Moreover, it has been reported that mast cells promote small bowel cancer progression in a tumor stage-specific and cytokine-dependent manner [96]. The role of IL-9 and IL-9 producing cells in antitumor immunity is summarized in Fig.…”
Section: Mast Cells In Tumor Immunitymentioning
confidence: 99%
“…Interestingly, the hallmark of IBD is a dysregulated intestinal immune response in which mast cells (MCs) accumulate in the inflamed gut of IBD patients [2]. Meanwhile, the report by Vivinus et al [3] showed that increased MCs numbers were counted in the colon of both Crohn's Disease (CD) and Ulcerative colitis (UC) patients compared to that in healthy controls, while activation of MCs are suggested by increased expression or release of MCs mediators in the mucosa, including proteases [4], histamine [5], chemokines and cytokines [6], leading to the attraction of inflammatory cells, changes in barrier function, tissue remodeling etc. However, the specific function of MCs in IBD development remains to be elucidated, especially the aberrant interactions between MCs and IECs or others underlying resident cells, which is fundamental for immunopathological regulation.…”
Section: Introductionmentioning
confidence: 99%